Preparation and Properties of SnO2 Film Deposited by Magnetron Sputtering - Dan Leng; Lili Wu; Hongchao Jiang; Yu Zhao; Jingquan Zhang; Wei Li; Lianghuan Feng (International Journal of Photoenergy)
Tin oxide SnO2 films were prepared by RF magnetron sputtering. The effects of oxygen partial pressure percentage on the SnO2 property have been investigated to obtain relatively high-resistivity SnO2 films which could be used as buffer layers to optimize the performance of CdTe/CdS solar cells. The oxygen partial pressure percentage varied in the range of 1%~10%. The results show that the introduction of oxygen would suppress the deposition and growth of SnO2 films. Electrical measurement suggests that the film resistivity decreases with the increase of oxygen pressure. The SnO2 films with resistivity of 232 Ω cm were obtained in pure Ar atmosphere. All SnO2 films fabricated with different oxygen partial pressure percentage have almost the same optical band gap.